Hypothetical integration in a social accounting matrix and fixed-price multiplier analysis - Kijong Kim (Levy Economics Institute of Bard College, 2008)
This study proposes a simple modification to a Social Accounting Matrix (SAM) in order to analyze the multiplier effects of a new sector. A different input composition, or technology, of the sector makes a conventional analysis of final-demand injections on existing sectors invalid. We show that the modificationso-called hypothetical integrationis an efficient way to incorporate the difference into the SAM, rather than costly full-scale rebalancing. We apply this method to the case of the Expanded Public Works Programme in South Africa, and show that the proposed approach effectively represents the labor intensity requirement of the program and a new-factor income distribution.
Keywords: C67; D57; E24; E62; H51; H52; 330; Hypothetical integration; multiplier analysis; social accounting matrix; social sector intervention; Expanded Public Works Programme; South Africa